2011
DOI: 10.1001/archinternmed.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Treatment of Urinary Tract Infections in Two Rhode Island Nursing Homes

Abstract: Opportunities exist to improve provider practice related to the appropriate treatment of urinary tract infections in the nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 27 publications
3
101
1
1
Order By: Relevance
“…32 However, previous research has consistently documented that 25%-75% of antibiotic treatments in long-term care facilities are inappropriate. 4,5,55 CMAJ | JUNE 26, 2017 | VOLUME 189 | ISSUE 25 E859…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 However, previous research has consistently documented that 25%-75% of antibiotic treatments in long-term care facilities are inappropriate. 4,5,55 CMAJ | JUNE 26, 2017 | VOLUME 189 | ISSUE 25 E859…”
Section: Limitationsmentioning
confidence: 99%
“…[4][5][6] As a result, vulnerable residents of these facilities are exposed to avoidable harms that range from allergy to organ-specific toxicities, 4,7 Clostridium difficile infection 8,9 and antimicrobial-resistant pathogens. 10,11 Many harms affect not only the direct recipients of these drugs but also neighbouring and future residents of the facility.…”
mentioning
confidence: 99%
“…Because C. difficile is highly prevalent, unnecessary antimicrobials pose significant risk. In fact, Rotjanapan et al reported that residents who received an antimicrobial for a UTI not meeting the McGeer criteria had eightfold greater odds of developing a C. difficile infection relative to other nursing home residents [54]. Overall, 12 % of 96 residents who received antibiotics for a suspected UTI developed C. difficile infection within 3 weeks, compared to none of 76 who did not receive antibiotics [54].…”
Section: Consequences Of Unnecessary Antimicrobial Usementioning
confidence: 99%
“…In fact, Rotjanapan et al reported that residents who received an antimicrobial for a UTI not meeting the McGeer criteria had eightfold greater odds of developing a C. difficile infection relative to other nursing home residents [54]. Overall, 12 % of 96 residents who received antibiotics for a suspected UTI developed C. difficile infection within 3 weeks, compared to none of 76 who did not receive antibiotics [54]. Interventions pertaining to antimicrobial stewardship have been demonstrated to reduce C. difficile infections among nursing home residents [55].…”
Section: Consequences Of Unnecessary Antimicrobial Usementioning
confidence: 99%
“…10 Prospective studies have also shown an increase in adverse drug effects and the isolation of increasingly resistant bacteria among patients who received antimicrobial therapy for asymptomatic bacteriuria compared with those who did not. 8 In a recent randomized prospective trial involving 673 young women with asymptomatic bacteriuria, the occurrence of symptomatic urinary tract infection in the subsequent year was significantly higher among those who received treatment for asymptomatic bacteriuria than among those who did not (48.6% v. 13%, p < 0.001).…”
Section: Decisionsmentioning
confidence: 99%